Meningkatkan Kompetensi Pedagogik Guru dalam Penggunaan Media Pembelajaran Digital pada Masa Adaptasi Kabiasaan Baru (AKB) terhadap Hasil Belajar Tematik di SDN 77/X Parit Culum 1 Tahun 2020/2021 - Darmanelis Darmanelis (Jurnal Ilmiah Dikdaya, 2022)
Mastery of these skills allows teachers to be able to manage learning activities more effectively during the Adaptation of New Habits (IMR). By mastering skills in the use of digital learning media, teachers are expected to be able to improve the quality of the learning process so that the quality of education can be realized properly. This study aims to improve the skills of teachers in the use of digital learning media in elementary schools grades I, II and III at SDN 77/X Parit Culum I, Muara Sabak Barat District, Tanjung Jabung Timur Regency in implementing thematic learning. This type of research is qualitative. This research was carried out at SD Negeri 77/X Parit Culum I Muara Sabak Barat, the research sample was grade I, II and III teachers. Based on the results of research on teacher skills in using digital learning media in explaining thematic learning at SD Parit Culum I Muara Sabak Barat, Tanjung Jabung Timur Regency. overall the Class Teachers at SDN 77/X Parit Culum I have carried out learning activities with digital learning media and are still in the ENOUGH category. It can be seen that Class I teachers get a percentage score of 56.25%. Then Class II teachers achieved a percentage value of 60%, and Class III teachers with a percentage value of 62.5%